Stories of the sharing economy: Policy narratives surrounding the entry of transportation network companies into four mid-sized American cities. Issue 3 (3rd July 2019) - Dupuis, Nicole
ABSTRACT: New transportation businesses such as Uber and Lyft have recently entered metropolitan markets across the US. Because they do not fit into existing regulatory and policy frameworks, and their entrance into markets is sometimes abrupt or illegal, these transportation network companies (TNCs) engender widely varying reactions from city governments. These reactions are captured in different stories that develop about TNCs when they enter a market. Using content analysis, elements of the narrative policy framework (NPF), and application of Mark Bevir and R.A.W. Rhodes decentered theory of governance, this study explores the narratives that develop about TNCs and how those narratives may influence policy making. Prominent themes that emerged from an analysis of city council meetings in four mid-sized American communities include safety, leveling the playing field, and market considerations. There was also an identifiable causal linkage between the types of stories councilmembers told, and the solutions they proposed in deliberations. Finally, this article makes a compelling argument for the compatibility of the NPF and Bevir and Rhodes interpretivist tradition by pointing out the similarities among the two, and demonstrating ways in which they can effectively dovetail in narrative analysis.